Assessment of Air Pollution Trends in Jos Metropolis Using Ground Observations - Kamaludeen, Adamu Muhammad; Yusoff, Izham Bin Mohamad; Gidado, Suleiman Mohammed (Journal of Neonatal Surgery, 2025)
This study examines air pollution in Jos Metropolis, Plateau State, Nigeria, focusing on PM10, PM2.5, SO2, and CO levels from September to December in 2023 and 2024. Data from six monitoring stations reveal significant diurnal and seasonal variations, with higher pollutant concentrations in the morning due to peak vehicular and industrial activities. Findings indicate a rise in PM2.5 and CO levels in 2024, particularly in Jos North, linked to urbanization, increased vehicle emissions, and biomass combustion. CO levels surged from 11.82 ppm in 2023 to 27.48 ppm in 2024, emphasizing worsening air quality. The study underscores the contribution of human activities, including fuel combustion, industrial processes, and inadequate waste management, to air pollution trends in the region. To mitigate pollution, strategic interventions such as enforcing stricter emissions regulations, promoting cleaner energy alternatives, and improving public transport systems are recommended. Public awareness campaigns on air pollution and sustainable waste management should also be encouraged. Without effective measures, deteriorating air quality could lead to severe health implications for residents. This study provides critical insights into air pollution trends in Jos Metropolis, serving as a foundation for further research and policy development aimed at improving urban air quality in Nigeria.